MENDORONG PERILAKU ETIS TENAGA PENJUALAN MELALUI GAYA KEPEMIMPINAN MANAJER PENJUALAN - Wardati, Emi (STIE Totalwin Semarang, 2014)
A significant amount of research has focused on the ethical dilemmas facing business-to-business salespeople and the conflicts these salespeople face in making decisions on how best to represent and sell their products. A number of studies have identified the common implications that result as a consequence of ethical or unethical behavior, but few studies have made an attempt to understand the factors that lead to ethical salesperson intentions. The present study empirically examines antecedents of ethical salesperson behavior.